2005
DOI: 10.1007/s10531-004-0314-y
|View full text |Cite
|
Sign up to set email alerts
|

Saproxylic Beetles in Standing Dead Wood Density in Relation to Substrate Sun-exposure and Diameter

Abstract: Species-specific densities of saproxylic beetles in cut 4-m high, medium to large diameter stumps of spruce, birch, aspen and oak were monitored for 7 years after cutting, by trapping emerging insects within seasonally applied net enclosures. A total of 47,038 individuals, representing 316 saproxylic beetle species including 40 red-listed species, were recorded. Densities of 86 species were modelled in relation to stump diameter and measured levels of sun-exposure. Two thirds of the species favoured semi-or fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
111
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(128 citation statements)
references
References 29 publications
12
111
2
3
Order By: Relevance
“…LR type had a greater explanatory power than LR diameter, possibly because LR type was more strongly correlated with unstudied variables, such as the presence or absence of needles on particular LR fragments. Substrate diameter has previously been shown to affect saproxylic beetle occurrence (Schiegg 2001, Lindhe & Lindelöw 2004, Lindhe et al 2005, Jonsell et al 2007, Maňák 2007, Jonsell 2008b, Foit 2010, Brin et al 2011. Thus, nine taxa were signifi cantly associated with LR diameter in the present study ( Table 2).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…LR type had a greater explanatory power than LR diameter, possibly because LR type was more strongly correlated with unstudied variables, such as the presence or absence of needles on particular LR fragments. Substrate diameter has previously been shown to affect saproxylic beetle occurrence (Schiegg 2001, Lindhe & Lindelöw 2004, Lindhe et al 2005, Jonsell et al 2007, Maňák 2007, Jonsell 2008b, Foit 2010, Brin et al 2011. Thus, nine taxa were signifi cantly associated with LR diameter in the present study ( Table 2).…”
Section: Discussionsupporting
confidence: 54%
“…In general, the occurrence of saproxylic beetles on LRs or dead wood is affected by substrate characteristics, including substrate metric parameters, such as bark thickness (Zhang et al 1993, Foit 2010 and diameter (Schiegg 2001, Lindhe & Lindelöw 2004, Lindhe et al 2005, Jonsell et al 2007, Maňák 2007, Jonsell 2008b, Foit 2010. Sun exposure (Jonsell et al 2004, Lindhe & Lindelöw 2004, Lindhe et al 2005, Jonsell 2008b), moisture (Wallace 1953, Larkin & Elbourn 1964, decomposition stage (Wallace 1953, Vanderwel et al 2006, Jonsell 2008b and the presence of other organisms (Jonsell et al 2005, Abrahamsson et al 2008, Weslien et al 2011) are of remarkable signifi cance for the occurrence of saproxylic beetles in various substrates. Because of these associations, known breeding substrate requirements and timing of mating and egg laying of particular BWBB species (Schwenke 1972), it is possible that the colonisation of LRs by BWBBs is infl uenced by the date of LR production (felling date).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Perovich and Sibold [60] reported that stands with MPB outbreak had greater diversity in age classes and species composition. In addition, natural disturbances generate tremendous amounts of dead wood, which can be used as habitats for many saproxylic (i.e., organisms that depend, during at least part of their life cycle, upon the dead or dying wood of moribund or dead trees, or upon other saproxylic organisms) species [147]. Based on a study by Müller et al [148], European spruce bark beetle (Ips typographus) infestations improved the habitat of several endangered saproxylic beetles.…”
Section: Ecosystem Resiliencementioning
confidence: 99%
“…However, more sun-exposed oaks do on average host more species than more shaded ones (Ranius and Jansson 2000;Lindhe et al 2005;Buse et al 2007). Thus, to favour a larger number of species it might be advisable to place the boxes so that a variation in sun exposure is obtained.…”
Section: Box Usagementioning
confidence: 99%